Liability of corporations in Italy and risk prevention: toward a cloud-governance system. (1st January 2013) - Gaudenzi, Barbara; Lucietto, Gianluigi; Domenichini, Pietro
This research describes the Italian regulation on liability of corporations (Italian Legislative Decree 231 issued in 2001) and the consequent requirements in terms of risk management and corporate governance. Starting with an analysis of the literature on the relationships among governance, risk management and compliance, the paper investigates the new challenges emerging from this legislative scenario. Moreover, the paper describes the critical phases towards the implementation of a managerial risk management process that helps managers to monitor all the responsibilities imposed by the Decree. Finally, the paper analyses when and how cloud-based solutions can support companies in managing critical risks, and particularly those risks that are formally mentioned by the Italian regulation on liability of corporations.